Metode Pembelajaran Al-Ashwat - Mufidah, Nuril (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
Abstract In Arabic learning, al-Ashwat plays an essential role because al-Ashwat or phonetic is a crucial element in every language. If al-Ashwat is not well understood, Arabic proficiency cannot be mastered perfectly. Often there will be a lack of understanding in the language process. So that the communication process will also be hampered. Learning methods are a way or means to present subject matter. With learning, the approach can simplify and accelerate the learning process towards understanding. There are at least two learning methods that pay attention to the teaching of sound language, including Phonetic Method and Mim-mem Method which is better known as an Audio-Lingual Method. Keywords: Arabic, al-Ashwat, Learning methods Anwar, Drs. H Tayar dan Drs. Syaiful, Metodologi Pengajaran Agama Dan Bahasa Arab (Jakarta: PT Raja Grafindo Persada)Chaer, Abdul, Linguistik Umum (Jakarta: Rineka Cipta, 2012)Dahlan, Juwairiyah, Metode Belajar Mengajar Bahasa Arab (Surabaya: AlIkhlas) Fakhrurrizi, Aziz dan Erta Mahyudin, Pembelajaran Bahasa Arab (Jakarta: Direktorat Jendral Pendidikan Islam Kementerian Agama RI, 2012) Hamid, M. Abdul, & H. Bisri Mustofa, Metode Dan Strategi Pembelajaran Bahasa Arab (Malang: UIN-MALIKI Press, 2012) Lundeto, Adri, „Analisis Metode Pengajaran Fonetik Dan Morfologi Bahasa Arab‟, Jurnal Iqro’ STAIN Manado, 2009, 13Meidar G. Arsyad mukti US, Pembinaan Kemampuan Berbicara Bahasa Indonesia (Jakarta: Erlangga)Nasution, Ahmad Sayuti Anshari, Bunyi Bahasa (Jakarta: Amzah, 2010)Nurbayan, Yayan, Metodologi Pembelajaran Bahasa Arab (Bandung: Zein AlBayan) Rosyidi, Abdul Wahab, Media Pembelajaran Bahasa Arab (Malang: UINMALIKI Press, 2009) ______________________, Ilmu al-Ashwat an-Nuthqi, (Rabith ‘Utsman) Sanjaya, Wina, Strategi Pembelajaran Berorientasi Standar Proses Pendidikan (Jakarta: Kencana Prenada Media, 2011) Syafrawi, Aziz Syafrudin dan Hasan Saefuloh, Pembelajaran Tata Bunyi (Ashwat) Bahasa Arab, 2014Tontowi, M., „Fonologi Dalam Pedidikan Dan Pelatihan Bahasa Arab Guru MI Tingkat Dasar Pada Diklat Keagamaan Kota Palembang‟Virdyna, Nina Khayatul., Penerapan Metode Fonik dalam Pembelajaran Bahasa Inggris bagi Anak Usia Dini, Jurnal Okara, 2015